Wearing an Ostomy Pouch and Becoming an Ostomate: A Kairological Approach to Wearability. Issue 3 (26th May 2016) - Kessler, Molly Margaret
Abstract : In both popular and scholarly discourse, wearable technologies are characterized primarily as technologies that quantify, providing wearers with new knowledge about themselves and their environments. Such limited characterizations do not fully engage technologies that are, indeed, wearable but do not simply quantify. This essay argues that wearability encompasses rhetorical work beyond that of popular, mainstream technologies like fitness trackers and sleep monitors. Using Judy Segal's "kairology, " this essay traces five ostomy pouch narratives—focusing on narratives of empowerment and constraint and analyzing competing experiences of wearing and the divergent identifications those experiences support. The essay concludes with preliminary insights into how kairology is well-suited to help researchers tease out the dynamic processes between wearer and technology, as well as the identities that those processes make possible.